Long-term implications of sustained wind power growth in the United States: Direct electric system impacts and costs. (1st October 2016) - Lantz, Eric; Mai, Trieu; Wiser, Ryan H.; Krishnan, Venkat
Highlights: 35% wind energy in the U.S. requires approximately 400 GW of wind power capacity. 35% wind energy in the U.S. supports reduced natural gas and coal generation. Long-term (2050) retail rate reductions (2%) from wind energy are observed. Cumulative electric sector savings (3%) from wind energy are observed. Transmission needs are estimated to be on par with historical demand since 1990. Abstract: This paper evaluates potential changes in the power system associated with sustained growth in wind generation in the United States to 35% of end-use demand by 2050; Wiser et al. (2016) evaluate societal benefits and other impacts for this same scenario. Under reference or central conditions, the analysis finds cumulative wind capacity of 404 gigawatts (GW) would be required to reach this level and drive 2050 incremental electricity rate and cumulative electric sector savings of 2% and 3% respectively, relative to a scenario with no new wind capacity additions. Greater savings are estimated under higher fossil fuel costs or with greater advancements in wind technologies. Conversely, incremental costs are found when fossil fuel costs are lower than central assumptions or wind technology improvements are more-limited. Through 2030, the primary generation sources displaced by new wind capacity include natural gas and coal-fired generation. By 2050, wind could displace other renewables. Incremental new transmission infrastructure totaling 29 million megawatt-miles is estimated to be needed by 2050. In conjunction with related societal benefits, this work demonstrates that 35% wind energy by 2050 is plausible, could support enduring benefits, and could result in long-term consumer savings, if nearer-term (pre-2030) cost barriers are overcome; at the same time, these opportunities are not anticipated to be realized in their full form under "business-as-usual" conditions.